Анализ проблемы защиты бытовых однофазных потребителей от недопустимых отклонений напряжения в питающей сети - Чепелюк, Александр Александрович; Хлобыстин, А. Л. (НТУ "ХПИ", 2012)
Проведен анализ проблемы защиты бытовых однофазных потребителей электрической энергии от недопустимых отклонений напряжения в питающей сети.

Analysis of the problem concerning to protection of household single-phase consumers of electric energy from inadmissible deviations of voltage in the electric power line is resulted.
Protection of household single-phase consumers against inadmissible deviations of the power line voltage
Keywords: энергия электрическая; электроснабжение; качество; электрооборудование; single-phase consumers; power line; voltage; deviations; protection